Impact of severe obesity on exercise performance in heart failure with preserved ejection fraction. Issue 22 (18th November 2020) - Sarma, Satyam; MacNamara, James; Livingston, Sheryl; Samels, Mitchel; Haykowsky, Mark J.; Berry, Jarett; Levine, Benjamin D.
Abstract: Background: Obesity plays an important role in functional impairment in HFpEF. The mechanisms underlying decreased functional capacity in obese HFpEF are not clear. We assessed the cardiac and peripheral determinants of exercise performance in HFpEF patients with class 2 obesity in the upright position, representative of posture when performing functional activities. Methods and Results: Thirty‐two HFpEF patients were divided into two groups by presence of class 2 obesity (C2, BMI ≥ 35 kg/m 2, n  = 14) and non‐C2 (BMI < 35 kg/m 2, n  = 18). Participants performed a bout of submaximal exercise followed by incremental stages of treadmill exercise to determine peak aerobic power (peak VO2 ). Peak VO2 and Ve/VCO2 were measured using Douglas bags while cardiac output (Qc) and stroke volume (SV) were measured by acetylene rebreathing. The C2 group were younger than the non‐C2 group (67 ± 6 versus 73 ± 6 years; p  = .009). Comorbid condition burden was similar between groups. Peak VO2 indexed to body mass was not significantly different between groups. Absolute peak VO2 was higher in the C2 group secondary to a larger peak Qc (14.3 versus 11.0 L/min; p  = .012). SV reserve was also higher in the C2 group (72 versus 49%; p  = .038). Conclusion: HFpEF patients with severe obesity had similar cardiorespiratory fitness compared to patients with lower BMI with similar comorbidity burden. Absolute VO2 was actually higher in the severely obese driven by larger Qc and SV reserve arguing against significant effects from obesity per se on aerobic performance. The presence of a larger "cardiac engine" may offer potential for fat‐loss strategies to improve impairments in functional capacity in obese patients with HFpEF. Abstract : Obesity is linked to decreased functional capacity in in patients with heart failure with preserved ejection fraction (HFpEF).The mechanisms responsible for decreased functional capacity are unclear. Our study demonstrated HFpEF patients with severe obesity have higher absolute VO2, a result of larger cardiac output and stroke volume reserve, highlighting a potential role for fat loss strategies to improve impairments in functional capacity.